A PROSPECTIVE INTERVENTIONAL COMPARATIVE LONG-TERM STUDY ON THE EFFICACY OF CANAGLIFLOZIN AND DAPAGLIFLOZIN IN A TERTIARY CARE HOSPITAL FOR A SPAN OF 1 YEAR - DHANUSH BELLAPU; RONALD DARWIN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study mainly focuses on the comparison between the efficacy of canagliflozin and dapagliflozin by observing the prolonged effects, quality of life of patients, and comparing them with patients prescribed antihyperglycemic agents other than sodium-glucose cotransporter-2 (SGLT-2) inhibitors. Methods: This prospective interventional comparative study was conducted among 3452 patients admitted to the general medicine and endocrine department, Anu Group of Hospitals, Vijayawada, for 1 year, by eluding the patient’s fasting blood sugar, postprandial blood sugar, renal function test, Hemoglobin A1c, blood pressure, and the finding severity score of adverse drug reaction (ADR) using the Naranjo scale during the study. Results: The most common ADRs after utilizing canagliflozin was hypotension and dapagliflozin wes dehydration. The Chi-square test for patients with ADR’s after using canagliflozin versus dapagliflozin used to treat type 2 diabetes. 9.12529 is the calculated Chi-square value at 5° of freedom and 5% level of significance (p<0.1042 – not significant). This shows that there was a slight difference but similar effects using canagliflozin versus dapagliflozin. The positive effect after treatment was weight reduction, which was greater in canagliflozin. Negative effects were hypotension, dehydration, infections, polyuria, and ketoacidosis, which were greater in canagliflozin. Conclusion: We concluded that females were affected by urinary tract infection and vaginal infection. Efficacy was similar in control, canagliflozin, and dapagliflozin, but it may be a cost-related burden.